Tantangan Pendidikan Sosiologi Di Era Industri 4.0 - Hamsah Hamsah; Sangputri Sidik; Romi Mesra; Rahmat Nur (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
This article is a study that highlights the various problems and challenges faced by the sociology education discipline in the Industrial 4.0 era. Included in it is to see the existence of sociology education in the midst of the current globalization. The method used in this writing is the method of literature by collecting various relevant research results. The conclusion of this study is that era 4.0 presents challenges to sociology education while providing opportunities if it is managed properly. Among the challenges are developments in information and communication technology, learning methods and curriculum changes.